The Capability of Three Final Irrigation Materials on apical leakage of Bioceramic Sealer Obturation after Calcium Hydroxide Cleaning - Tien Suwartini; Chandra Kristopano; Bernard Ongki Iskandar; Meiny Faudah Amin; Komariah (Faculty of Dentistry, Universitas Trisakti, 2025)
Background: Obturation is an important step in root canal treatment. Obturation has to result in a tight root canal closure and eliminate all apical and coronal connection pathways. Calcium hydroxide intracanal medicament residue left behind may interfere with the endodontic sealer penetration, and cause an apical leakage. Chitosan acetate 0,2% has been shown to have antibacterial effects and can remove the smear layer. Objective: To determine the effectiveness of different types of final irrigation on the apical seal of bioceramic sealer obturation after calcium hydroxide intracanal medicament cleaning. Method: The study is performed on a sample of lower first premolar teeth that have been prepared and filled with calcium hydroxide intracanal medicament paste. One week later, calcium hydroxide removal is performed with NaOCl. The samples were divided into 3 groups based on the final irrigation material prior to obturation: group 1 was irrigated with 2.5% NaOCl, group 2 with 17% EDTA, and group 3 with 0.2% chitosan acetate. All samples were obturated using the single cone technique and bioceramic sealer and then immersed in Indiana ink. Apical leakage was measured based on the deepest penetration of the dye into the root canal. Results: The smallest apical leakage value was the final irrigation group with 0.2% Chitosan Acetate, and the apical leakage value of the 2.5% NaOCl group was the same as 17% EDTA, but there was no statistically significant difference between the three study groups. Conclusion: There is no difference in the effectiveness of final irrigation between EDTA 17% and chitosan-acetate 0.2% on the apical seal of bioceramic sealer obturation after calcium hydroxide removal. Chitosan-acetate 0.2% can be used as an alternative as a final irrigation material for root canals after calcium hydroxide intracanal medicament, in obturation using a bioceramic sealer.